Cell membrane penetration and mitochondrial targeting by platinum-decorated ceria nanoparticles. Issue 27 (24th June 2016) - Torrano, Adriano A.; Herrmann, Rudolf; Strobel, Claudia; Rennhak, Markus; Engelke, Hanna; Reller, Armin; Hilger, Ingrid; Wixforth, Achim; Bräuchle, Christoph
Abstract : Platinum-decorated ceria nanoparticles of ∼50 nm can rapidly penetrate cell plasma membranes and reach intracellular organelles, such as mitochondria. Abstract : In this work we investigate the interaction between endothelial cells and nanoparticles emitted by catalytic converters. Although catalyst-derived particles are recognized as growing burden added to environmental pollution, very little is known about their health impact. We use platinum-decorated ceria nanoparticles as model compounds for the actual emitted particles and focus on their fast uptake and association with mitochondria, the cell's powerhouse. Using live-cell imaging and electron microscopy we clearly show that 46 nm platinum-decorated ceria nanoparticles can rapidly penetrate cell membranes and reach the cytosol. Moreover, if suitably targeted, these particles are able to selectively attach to mitochondria. These results are complemented by cytotoxicity assays, thus providing insights into the biological effects of these particles on cells. Interestingly, no permanent membrane disruption or any other significant adverse effects on cells were observed. The unusual uptake behavior observed for 46 nm nanoparticles was not observed for equivalent but larger 143 nm and 285 nm platinum-decorated particles. Our results demonstrate a remarkable particle size effect in which particles smaller than ∼50–100 nm escape the usual endocytic pathway and translocate directly into the cytosol, while particles larger than ∼150 nm are internalized by conventional endocytosis. Since the small particles are able to bypass endocytosis they could be explored as drug and gene delivery vehicles. Platinum-decorated nanoparticles are therefore highly interesting in the fields of nanotoxicology and nanomedicine.